Kualitas Fisik Dan Organoleptik Nugget Ayam Dengan Fortifikasi Tepung Daun Kelor (Moringa oleifera L) - Hendro Priyono; Sri Lestari; Yusnaini Yusnaini (Cannarium, 2022)
Nugget is one of food product mostly made from meat that widely liked by people in all ages especially by children. It is easily to modify the ingredients thus it has many varieties. This research was aimed to evaluate the effect  of Moringa oleifera L leaf flour fortification on chicken nuggets in terms of physical and organoleptic qualities. The data of physical qualities (cooking loss and tenderness) and organoleptic qualities (texture and taste) were analyzed for variance completely randomized design followed by the least significant different test (LSD). The results showed that Moringa oleifera leaf flour fortification on chicken nugget affected the tenderness and taste of it, but it had no effect on the cooking loss and texture qualities. Chicken nugget with addition of 1% Moringa oleifera leaf flour was the best product of all.Keywords: physical qualities, organoleptic qualities, fortification, Moringa oleifera leaf  flour, chicken nugget